The Role of Leadership Style in Shaping Employee Performance - Laksmita, Venda Arsenia; Perdhana, Mirwan Surya (LifeSciFi, 2024)
Employee performance is assessed based on the results achieved in carrying out tasks according to their responsibilities. The quality of performance is influenced by the ability to carry out tasks in accordance with the given role. Improving employee performance requires a leadership style that can influence and direct organizational activities and facilitate the achievement of goals. In multigenerational teams, understanding diverse viewpoints and preferences is crucial to leadership effectiveness. This research investigates the role of leadership style in shaping employee performance, with a focus on multigenerational teams within environmentally sound finance and investment organizations. Using a blended method approach, this study examines how different leadership styles affect employee performance. The central variables of organizational culture serve as mediators in understanding the relationship between leadership style and employee performance. This study uses qualitative and quantitative methods to collect comprehensive insights into the dynamics that occur. By exploring the interplay between leadership styles, organizational culture, and employee performance, this research contributes to a deeper understanding of effective leadership strategies in the context of diverse workforce demographics and environmentally friendly organizational practices.